(untitled) (Revista cientifica In Vestigium Ire, 2016)
This article puts in a nutshell what is expressed in a book with a similar title, developed by the authors and is also being published. In this paper develops a way to structure formative research projects in which special emphasis on the problem description with facts, figures and statistics for clarity in its approach is made. Steps are then presented to relate the history and state of the art and how to properly prepare project justification, emphasizing the human, social and environmental impact is required. Also presents a way to develop objectives, ingredients and the importance of checking the feasibility of the project is explained. Likewise, the central aspects relate to develop the theoretical framework, the methodological framework and the budget timeline. Finally, the way the literature and how to present the citations is made is explained.